Layered Metal Hydroxides Exfoliation Assisted By Sugar Molecules And Physicochemical Characterisation Of The Nanosheets - Sivakumar, Mineesha (2024)
The exfoliation of layered metal hydroxides is highly favourable for the formation of single layer layered double hydroxide (LDH) and layered zinc hydroxide (LZH) nanosheets due to their unique chemical, thermal, optics, and biological properties. In this study, the exfoliation of layered double hydroxide (LDH) and layered zinc hydroxide (LZH) were performed using sugar molecules as an exfoliating agent in DMSO and water. The X-ray diffraction (XRD) suggest that LDH were successfully exfoliated and formed single layer nanosheet, indicated by the formation of single peaks. It is demonstrated that XRD patterns of LDH using 1g sucrose in DMSO via co-precipitation, reconstruction, and hydrothermal show the best diffraction pattern with only a single peak formed in all the exfoliated samples. The structural information of the exfoliated LDH in three different phases is further studied using XRD to reveal the extent of the exfoliation process. We examined the crystalline phase of LDH in different stages of liquid exfoliation; suspension, semi-dry suspension and dried solid samples. XRD data shows one broad peak for all the LDH exfoliated samples at 2θ = 23.9,22.4, and 22.3° respectively, which correspond to the characteristic (003) basal reflection of LDH single layers. These single peaks indicate the formation of LDH nanosheets. On the other hand, only XRD pattern of LZH exfoliated with 1g sucrose in water via hydrothermal exhibit the single peak while co-precipitation and reconstruction are not. Thus, only hydrothermal method in LZH indicates formation of nanosheets.